MODIFIED SINGLE ROLL FLAP APPROACH FOR SIMULTANEOUS IMPLANT PLACEMENT AND GINGIVAL AUGMENTATION - Kamen Kotsilkov (Peytchinski Publishing, 2017)
INTRODUCTION: The frequent result of tooth extraction is the resorption of the buccal alveolar wall and formation of I class (Siebert) alveolar ridge defect. Another frequent problem in the implant surgery after the elevation of the standard full thickness flap is the choice of the exact vertical implant position to provide adequate biological width with 3mm keratinized soft tissue above a bone level implant. Nowadays the aim is to develop minimally invasive surgical approaches for other surgical applications. AIM: This presentation demonstrates the application of a newly modified, minimally invasive, single roll flap approach for simultaneous implant placement and gingival augmentation. MATERIALS AND METHODS: A 47 years old patient presented with fractured left central incisor. A new surgical technique for simultaneous implant placement and gingival augmentation was applied. Buccal partial thickness flap was prepared with de-epithelization and roll flap elevation of the crestal keratinized tissue, thus forming new papillae and ensuring implant placement in the exact vertical position. After one week of healing the final screw retained restoration was placed. RESULT: The application of this newly developed by the author modification of the surgical protocol allowed precise implant placement consistent with the biological width requirements and simultaneously achieving buccal gingival augmentation. CONCLUSION: The proposed new surgical approach provides an opportunity for minimally invasive implant placement without periosteal elevation. The modified roll flap preserves the keratinized tissues of the alveolar ridge using them to provide adequate buccal soft tissue volume. Furthermore, this approach ensures precise selection of the optimal implant depth, thus providing maximal functional and aesthetic result.